An Observational Study of Inhaled-Treprostinil Respiratory-Related Safety in Patients with Pulmonary Arterial Hypertension. (September 2016) - Zamanian, R. T.; Levine, D. J.; Bourge, R. C.; De Souza, S. A.; Rosenzweig, E. B.; Alnuaimat, H.; Burger, C.; Mathai, S. C.; Leedom, N.; DeAngelis, K.; Lim, A.; De Marco, T.
Inhaled treprostinil (Tyvaso) has been shown to be a safe and effective addition to pulmonary arterial hypertension (PAH) oral therapies; however, the respiratory-related safety profile of inhaled treprostinil required further elucidation in the setting of routine clinical care. The objectives of this study were to characterize respiratory-related adverse events (AEs) associated with current or recent treatment with inhaled treprostinil and to compare the incidence of respiratory-related AEs in PAH patients treated with inhaled treprostinil with that in patients treated with other Food and Drug Administration (FDA)–approved PAH therapies. This was a long-term, prospective, observational study. All respiratory-related AEs were recorded during the study. The number of PAH patients enrolled was 1, 333, 666 treated with inhaled treprostinil and 667 controls (treated with an FDA-approved PAH therapy other than inhaled treprostinil), for a total of 958 and 1, 094 patient-years of exposure, respectively. In the inhaled-treprostinil group, 1, 281 respiratory-related AEs were reported in 403 patients (61%), and in the control group, 1, 295 respiratory-related AEs were reported in 388 patients (58%). Cough, throat irritation, nasal discomfort, and hemoptysis were the most common respiratory-related AEs (occurring in ≥2% of patients in either treatment group) that demonstrated a higher number of events per patient-year of exposure in the inhaled-treprostinil group than in the control group (risk ratio [95% confidence interval]: 1.487 [1.172–1.887], 3.777 [2.050–6.956], 2.039 [1.072–3.879], and 1.957 [1.024–3.741], respectively). Overall, inhaled treprostinil was well tolerated by PAH patients in routine clinical care, with respiratory-related AEs consistent with the known safety profile (trial registration:clinicaltrials.gov identifier: NCT01266265).